Analysis of Sharia-Based Hotels on Sustainable Tourism in West Sumatera Indonesia - Bundo, Mayang; Pratama, Fahmi Achta (Journal of Islamic Economics and Finance Studies, 2024)
Tourism is a potential sector in the world, especially halal tourism which is a potential market for Muslim tourists, especially Indonesia, and more specifically West Sumatera. Because this province has the potential for halal tourism because it is included in the halal destinations listed in the 2015/2025 National Tourism Development Master Plan (Rencana Induk Pembangunan Kepariwisataan Nasional/Ripparnas). Furthermore, one of the sub-subs of halal tourism is sharia-based hotels which support tourists to stay overnight. Then, in tourism theory there is the term sustainable tourism, tourism that has an effect on economic, environmental and social aspects. The aim of this research is to scientifically determine the influence of Sharia-based hotels on sustainable tourism development in West Sumatera. This research is combination research that used mixed method. Quantitative method using questionnaires and also qualitative using analytical descriptive. The research results show that Sharia-Based Hotels have a positive influence on Sustainable Tourism in West Sumatera, including economic, environmental and social aspects. The increase in Sharia-Based Hotels is directly proportional to the increase in Sustainable Tourism.